Enhancement of the Heat Transfer Efficiency of Closed Wet Cooling Tower by a Water Spray Method - Tongorn, Siripol; Rewlay-ngoen, Chantima; Papong, Seksan (Food Agricultural Sciences and Technology, 2021)
This research aimed to enhance the heat transfer efficiency of 200 TR (Ton of Refrigeration) closed wet cooling tower. According to the study, it was found that one factor that had effects on heat transfer was atmosphere temperature during 01:00-04:00 p.m. Summer temperature in Thailand which is higher than 36 ºC reduces the efficiency of heat transfer. To solve this problem, the researcher enhanced the efficiency by reducing the temperature around thermoelectric coolers by spraying water particles between 20–70 micron with a water flow rate of 20 liters per minute and spray distance of 20, 30, 40, 50, and 60 centimeters. The results showed that at the spray distance of 30 centimeters, the temperature could be reduced to a maximum of about 2.74 ºC. Secondly, a spray distance of 40 centimeters could reduce the temperature by approximately 2.23 ºC. Lastly, at the distance of 20 and 50 centimeters, the temperature was approximately reduced 2 .06 ºC and 1.68 ºC, subsequently. However, a spray distance of 60 centimeters could not reduce the temperature of heat exchange. When analyzing a break-even point, it was found that a payback period was about seven months. These results could be applied as guidelines to enhance the efficiency of heat transfer in factories, but the water flow rate used for spraying should be additionally studied.